2020
DOI: 10.1101/2020.05.15.098368
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clonal Heterogeneity Supports Mitochondrial Metabolism in Pancreatic Cancer

Abstract: Pancreatic ductal adenocarcinoma (PDA) is characterized by a heterogenous and densely fibrotic microenvironment. This limits functional vasculature and diffusion of nutrients through the tumor 1,2 . Accordingly, pancreatic cancer cells develop numerous metabolic adaptations to survive and proliferate in nutrient austere conditions 3-7 . Subtypes of PDA have been characterized by transcriptional and functional differences [8][9][10][11][12] , which have been reported to exist within the same tumor 13-15 . Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…Recently, the same group found that the ability of asparagine to activate mTORC1 represents a key adaptive strategy for tumor cells to mitigate ETC inhibition-induced stress, which is coupled to ATF4 activation [ 84 ]. This work provides an alternative explanation for the synergy between ETC inhibition and asparagine restriction [ 79 ] ( Figure 3 A), and also brings up the question of whether asparagine or aspartate is the most limiting metabolite to drive ETC inhibition-associated phenomenon in tumor cells. Furthermore, in addition to functioning as an exchange factor for mTORC1 activation, asparagine can also activate mTORC1 directly through an ADP-ribosylation factor 1 (Arf1)-dependent but Rag GTPase-independent mechanism [ 85 ] ( Figure 3 A).…”
Section: The Role Of Asparagine In Other Types Of Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, the same group found that the ability of asparagine to activate mTORC1 represents a key adaptive strategy for tumor cells to mitigate ETC inhibition-induced stress, which is coupled to ATF4 activation [ 84 ]. This work provides an alternative explanation for the synergy between ETC inhibition and asparagine restriction [ 79 ] ( Figure 3 A), and also brings up the question of whether asparagine or aspartate is the most limiting metabolite to drive ETC inhibition-associated phenomenon in tumor cells. Furthermore, in addition to functioning as an exchange factor for mTORC1 activation, asparagine can also activate mTORC1 directly through an ADP-ribosylation factor 1 (Arf1)-dependent but Rag GTPase-independent mechanism [ 85 ] ( Figure 3 A).…”
Section: The Role Of Asparagine In Other Types Of Cancermentioning
confidence: 99%
“…The ability of asparagine to modulate tumor progression can also be reflected at the stage when tumor cells respond to therapeutics. A recent study (in preprint) shows that clonal heterogeneity within a tumor tissue can contribute to therapeutic resistance through asparagine biosynthesis [ 79 ]. In a mouse pancreatic tumor model, the authors discovered metabolic heterogeneity within a tumor tissue, which leads to differential responses to electron transfer chain inhibitors (ETCi).…”
Section: The Role Of Asparagine In Other Types Of Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…These data support the existence of a GABA shunt-centric inter-tumoral metabolic heterogeneity among the ACC cohort. Interestingly, an intra-tumoral heterogeneity of GABA levels has recently been reported in clonal cell lines of distinct metabolic phenotypes (e.g., glycolytic vs mitochondrial) derived from single tumor ex vivo mouse pancreatic cancer cells [ 50 ]. Evaluation of both intra- and inter-tumoral heterogeneity of the GABA shunt may be important for understanding its role in mitochondrial metabolic heterogeneity, a feature of tumors that is increasingly recognized to influence cancer growth, progression, and drug treatment sensitivity [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown upregulation of asparagine synthetase (ASNS) (Williams et al, 2020) or aspartate/glutamate transporter SLC1A3 (Sun et al, 2019b) as resistance mechanisms to asparaginase in several solid tumor types. Another study has reported that Asn metabolism mediates resistance to OXPHOS inhibitors in PaC (Halbrook et al, 2020) and identifies Asndepleting modalities (genetic silencing of ASNS and depletion of exogenous Asn upon asparaginase treatment) as potential therapeutic strategies to re-sensitize pancreatic tumor cells to phenformin treatment. In addition, it has been shown that Phenformin is a genuine tumor disruptor not only by producing hypoglycemia due to caloric restriction via energysensing AMP-activated protein kinase, but also as a blocker of the mTOR regulatory complex (Rubiño et al, 2019).…”
Section: Amino Acid Metabolism In Cancer Cells and Therapy Resistancementioning
confidence: 99%